2017
DOI: 10.1177/0194599817700371
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry Analysis of CD44, EGFR, and p16 in Oral Cavity and Oropharyngeal Squamous Cell Carcinoma

Abstract: Objectives We analyze the relationship between CD44, epidermal growth factor receptor (EGFR), and p16 expression in oral cavity and oropharyngeal cancers in a diverse population. We also describe whether particular patterns of staining are associated with progression-free survival and overall survival. Study Design Prospective study, single-blind to pathologist and laboratory technologist. Setting Hospital based. Subjects and Methods Immunohistochemistry, comprising gross staining and cellular expression, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…Patients who were CD44+/p16− displayed the worst, and those who were CD44−/p16+ showed the best survival rates and LRC among all the groups. Our findings imply that combination of CD44 and p16 expression improves prognostic stratification of patients with OPSCC, supporting the suggestion of Cohen et al Nevertheless, results of multivariable analysis suggest dominant impact of p16 expression on the survival rates, supporting prior published data…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Patients who were CD44+/p16− displayed the worst, and those who were CD44−/p16+ showed the best survival rates and LRC among all the groups. Our findings imply that combination of CD44 and p16 expression improves prognostic stratification of patients with OPSCC, supporting the suggestion of Cohen et al Nevertheless, results of multivariable analysis suggest dominant impact of p16 expression on the survival rates, supporting prior published data…”
Section: Discussionsupporting
confidence: 92%
“…The cutoff on 90% of CD44 immunopositive cells with at least moderate intensity of immunostaining significantly identified patients with worse prognosis. Our findings were supported by recent work of Cohen et al, which introduced so‐called gross staining designation and reported worse OS in patients displaying universal gross staining designation defined by the presence of 90% of tumor showing the same localization of membrane or cytoplasmic CD44 expression. Negative prognostic effect of high expression of CD44 in oral and oropharyngeal cancers in terms of disease‐free survival and/or OS was also presented by Lindquist et al and Nasman et al In our study, patients with CD44+ OPSCC displayed significantly shorter OS and worse LRC on univariate analysis, supporting the results of Baschnagel et al and Motegi et al who reported high CD44 expression as a predictor for worse LRC, PFS and OS, and PFS and LRC rates significantly longer in CD44− patients, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings corroborate with previous studies about p16 expression in oral cavity SCC. It is estimated that about 44% up to 98% present high p16 expression [16,28,29,32,36]; in our study, the percentage of case with high p16 expression was of 61.3%. Studies that investigated the p16 expression in BSCC exclusively of the oral cavity are also rare.…”
Section: Discussionmentioning
confidence: 38%
“…On the contrary, in our study we did not find association between smoking habit or alcohol consumption in none of the variants studied. Several indexes are considered when studying the abnormal expression of p16 [16,28,29,32,33] and this fact compromises the interpretation and discussion with other studies. Furthermore, the initial studies about p16 overexpression are associated with HPV and are in cervix lesions [33][34][35].…”
Section: Discussionmentioning
confidence: 99%